Analisis Pemikiran Reflektif Guru Menggunakan Kuesioner Reflective Thinking for Teachers Questionnaire (RTTQ) - Rahayuningsih, Suesthi (BULLET : Jurnal Multidisiplin Ilmu, 2025)
This study aims to analyze the reflective thinking of Junior High School teachers in Mojokerto Regency, Mojokerto City, and Nganjuk Regency. The main focus of the research is to evaluate four dimensions of reflective thinking: lifelong learning skills, self-assessment abilities, self-belief and self-efficacy, and awareness of teaching skills.  A descriptive quantitative approach was employed to assess the level of teachers' reflective thinking at a specific point in time. Data were collected using the Reflective Thinking for Teachers Questionnaire (RTTQ), which was designed to measure the four dimensions mentioned above. Data analysis was conducted using descriptive statistics, t-tests, ANOVA, Pearson correlation, and boxplot visualizations.  The analysis revealed that most teachers responded positively to the dimensions of lifelong learning and self-assessment abilities, with average scores of 4.56 and 4.32, respectively. In contrast, the dimension of awareness of teaching skills received a considerably lower average score of 2.57, indicating the need for increased attention and reinforcement in this area. No significant differences were found based on gender or the subjects taught. Furthermore, the correlation between teaching experience and reflective teaching practices was weak, suggesting that other factors, such as institutional support, may play a more substantial role in shaping teachers’ reflective practices.  These findings underscore the importance of structured and continuous reflective training to enhance teachers’ awareness of their teaching skills. To strengthen the validity and scope of future studies, it is recommended that longitudinal research with a more diverse sample be conducted, in order to gain a more comprehensive understanding of the impact of reflective practices in various educational contexts.